Enterotoxigenic Escherichia coli Heat-Stable Toxin and Ebola Virus Delta Peptide: Similarities and Differences - Lilia I. Melnik; Robert F. Garry (Pathogens, 2022)
Enterotoxigenic Escherichia coli (ETEC) STb toxin exhibits striking structural similarity to Ebola virus (EBOV) delta peptide. Both ETEC and EBOV delta peptide are enterotoxins. Comparison of the structural and functional similarities and differences of these two toxins illuminates features that are important in induction of pathogenesis by a bacterial and viral pathogen.